2015
DOI: 10.1515/bpasts-2015-0093
|View full text |Cite
|
Sign up to set email alerts
|

Eigenproblems in nanomechanics

Abstract: Abstract. The paper is semitutorial in nature to make it accessible to readers from a broad range of disciplines. Our particular focus is on cataloging the known problems in nanomechanics as eigenproblems. Physical insights obtained from both analytical results and numerical simulations of various researchers (including our own) are also discussed. The paper is organized in two broad sections. In the second section the attention is focused on the analysis of quantum dots. The analysis of electronic properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…a model for the DNA writhing [12,13]. It is also demonstrated that for a small radius of the nanotubes the buckling mode falls into the regime of Euler beam buckling [14].…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…a model for the DNA writhing [12,13]. It is also demonstrated that for a small radius of the nanotubes the buckling mode falls into the regime of Euler beam buckling [14].…”
Section: Introductionmentioning
confidence: 89%
“…Microscopy measurements have significant meaning in examining the buckling of nanostructures. For instance, atomic force microscopy (AFM) is used to obtain the force-distance curve of nanotubes while buckling [9,14,15]. In situ transmission electron microscopy (TEM) also provides information on the characterisation of buckling [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation